The Effect of Contextual Teaching and Learning (CTL) Learning Models and Examples Non Examples on Learning Outcomes - Anton Eka Saputra; Jerni Siregar (Outline Publisher, 2023)
The problem in this research is the low result of learning to manage the office equipment AP class XI student of SMK Swasta Eria Medan. This study aims to determine the effect of learning models Contextual Teaching And Learning (CTL) and Examples Non Examples Of Learning Outcomes At Subjects Managing Office Equipment Class XI student of SMK Private Eria Medan T.P 2015/2016. This type of research is an experimental research. The population in this study were all students of class XI AP numbered 46 people. The sample in this study is the whole of the population that is class XI AP-1 (Experiment I) amounting to 23 people and XI AP-2 (Experiment II) amounting to 23 people. The research instrument used to collect data is shaped multiple-choice objective test which consist of 20 questions with five possible answers. It can be concluded that there is a positive and significant influence learning outcomes Managing Office Equipment by using model Contextual Teaching and Learning (CTL) and Examples Non Examples Of Student Results. And learning out comes by the use of learning models Contextual Teaching and Learning (CTL) with a percentage higher learning outcome by 54.81% compared with the learning outcomes of students who taught the learning model Examples Non Eamples with a percentage increase in learning outcomes by 51, 23% of the eyes lesson manage office equipment class XI AP SMK Swasta Eria Medan TP. 2015/2016.